Effect Of Additional Mineral of Potassium (K) in Low Salinity Culture Media on Performance of Vaname Shrimp Litopenaeus vannamei - Supono Supono; Putri Indah Suari; Munti Sarida (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
Potassium (K) is one of the important ions in low-salinity shrimp culture, which has functions of maintaining electrolyte balance, conduction of nerve impulses, and releasing energy from protein, fat, and carbohydrate. This research aimed to study and determine the proper concentration of potassium as an additive ion to enhance the growth and survival rate of vaname shrimp (Litopenaeus vannamei). Potassium was added to the rearing media with the salinity of 5 ppt in different concentrations (0, 50, 100, and 150 mg/L), with three replicates of treatment. The shrimp in size of post-larvae (PL)10 reared for 40 days in the treatment’s media with a stocking density of 140 shrimp (2000 shrimp/m3). The results of this study showed that potassium administration in low-salinity media has a significant effect on the growth performance and survival rate of shrimp. Potassium administration at a concentration of 100 mg/L resulted in better vaname performance than other treatments (P < 0.05) based on absolute weight, specific growth rate, feed conversion ratio, and survival rate